2012
DOI: 10.1530/eje-12-0454
|View full text |Cite
|
Sign up to set email alerts
|

Influence of hormonal control on LH pulsatility and secretion in women with classical congenital adrenal hyperplasia

Abstract: Objective: Women with classical congenital adrenal hyperplasia (CAH) exhibit reduced fertility due to several factors including anovulation. This has been attributed to a disturbed gonadotropic axis as in polycystic ovary syndrome (PCOS), but there is no precise evaluation. Our aim was to evaluate the gonadotropic axis and LH pulsatility patterns and to determine factor(s) that could account for the potential abnormality of LH pulsatility. Design: Case/control study. Methods: Sixteen CAH women (11 with the sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 30 publications
1
12
0
2
Order By: Relevance
“…In women, the present study showed the importance of hormonal control on the regularity of menstrual cycles and confirmed that CAH women do not necessarily present a disruption of the gonadotropic axis and anovulation as a result of early exposure to adrenal steroids, as we had previously shown (28). This is also in accordance with a study by Casteràs et al (29) which showed low fecundity in classic CAH patients but normal fertility in patients with parental project and spontaneous pregnancy in patients with strict control of progesterone concentrations in the follicular phase of the menstrual cycle.…”
Section: Discussionsupporting
confidence: 88%
“…In women, the present study showed the importance of hormonal control on the regularity of menstrual cycles and confirmed that CAH women do not necessarily present a disruption of the gonadotropic axis and anovulation as a result of early exposure to adrenal steroids, as we had previously shown (28). This is also in accordance with a study by Casteràs et al (29) which showed low fecundity in classic CAH patients but normal fertility in patients with parental project and spontaneous pregnancy in patients with strict control of progesterone concentrations in the follicular phase of the menstrual cycle.…”
Section: Discussionsupporting
confidence: 88%
“…However, high progesterone levels could contribute to female infertility 35 . In a case-control study of 16 women with classic CAH, those patients with a low LH pulse amplitude and frequency had higher progesterone levels and worse hormonal control than those with LH pulsatility similar to normal controls 36 . Further studies investigating the relevance of high progesterone in CAH and its impact on fertility are needed.…”
Section: Discussionmentioning
confidence: 93%
“…Several factors (androgen and progesterone overproduction and prenatal exposure to sexual steroid) are suspected to disturb the reproductive axis in CAH females. A recent study has described LH pulsatility in women with classic CAH (35). No differences have been observed between patients and controls in terms of mean LH levels, LH pulse amplitude or LH frequency.…”
Section: Female Fertilitymentioning
confidence: 94%